2018
DOI: 10.1016/j.ausmj.2018.07.003
|View full text |Cite
|
Sign up to set email alerts
|

When Nothing is What it Seems: A Digital Marketing Research Agenda

Abstract: Digital breakthroughs continue to challenge prevailing understandings of markets and marketing practices, bringing exciting opportunities to reimagine our offerings. Looking through the lens of digital surrealism, we identify key trends emerging in the field: (1) Is AR (Augmented Reality) for real?; (2) There is no better PR than GDPR (General Data Protection Regulation); (3) A persona is not a persona; (4) Min(e)d your language, and; (4 ¾) Raise your voice. Maybe. Based on these trends we develop an agenda fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 9 publications
1
38
0
5
Order By: Relevance
“…Additionally, studies indicated that customers could be primed to be in an assessment orientation state with advertisements (Mathmann et al 2017;Mannetti et al 2009). Retailers are encouraged to segment m-AR control and feedback mechanisms as part of their sensory-enabled retailing offerings to maximize consumer decision-confidence and comfort (Grewal, Roggeveen, and Nordfält 2017;de Ruyter, Keeling, and Ngo 2018).…”
Section: Implications For Retailersmentioning
confidence: 99%
“…Additionally, studies indicated that customers could be primed to be in an assessment orientation state with advertisements (Mathmann et al 2017;Mannetti et al 2009). Retailers are encouraged to segment m-AR control and feedback mechanisms as part of their sensory-enabled retailing offerings to maximize consumer decision-confidence and comfort (Grewal, Roggeveen, and Nordfält 2017;de Ruyter, Keeling, and Ngo 2018).…”
Section: Implications For Retailersmentioning
confidence: 99%
“…Fifita et al, 2015) as well as specific topics of interest to multiple disciplines. Examples of these are digital marketing (de Ruyter et al, 2018) and customer engagement (Abdul-Ghani et al, 2019). To extend the sports analogy, some consumers might be more interested in discussing team composition while others may be interested in discussing the mistakes of various umpires.…”
Section: Positioning Theoreticallymentioning
confidence: 99%
“…As customers start to engage in shared decision making with social AR, a fundamental premise is that both recommenders and decision makers feel comfortable with providing and accepting advice through the technology. This premise has not been systematically addressed in extant research and more insights are needed into the process and outcomes of using social AR (Hilken et al 2018;de Ruyter et al 2018). Relatedly, research offers little guidance on optimal AR configurations of sharing formats (photo or video) and communication modes (text and/or images) for firms wishing to support shared decision making (Javornik 2016;de Ruyter et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This premise has not been systematically addressed in extant research and more insights are needed into the process and outcomes of using social AR (Hilken et al 2018;de Ruyter et al 2018). Relatedly, research offers little guidance on optimal AR configurations of sharing formats (photo or video) and communication modes (text and/or images) for firms wishing to support shared decision making (Javornik 2016;de Ruyter et al 2018). Addressing these gaps in the knowledge base is pertinent as customer adoption and conversion rates for AR remain incremental and/or speculative (ARtillry 2019; Gartner 2018).…”
Section: Introductionmentioning
confidence: 99%